2018
DOI: 10.3349/ymj.2018.59.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Cancer Stem-Cell Markers OCT4, SOX2, and NANOG with Clinicopathological Features and Prognosis in Operative Patients with Rectal Cancer

Abstract: PurposeTo investigate the association of cancer stem-cell markers [octamer-binding transcription factor 4 (OCT4), sex determining region Y-box 2 (SOX2), and Nanog homebox (NANOG)] expression with clinicopathological properties and overall survival (OS) in operative rectal cancer (RC) patients receiving adjuvant therapy.Materials and Methods153 patients with primary RC receiving surgery were enrolled. Tumor tissue and paired adjacent normal tissue sample were collected, and OCT4, SOX2, and NANOG expressions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 39 publications
4
48
0
3
Order By: Relevance
“…It was reported that the stem cell associated genes, including OCT4, SOX-2 and Nanog and so on, have important roles in liver CSCs regulation. [25][26][27] As expected, miR-365 overexpression downregulated the expression of stemness-associated genes ( Figures 3A and 3B) and liver CSC markers in hepatoma cells ( Figures 3C and 3D), which further supported that miR-365 could inhibit liver CSCs expansion.…”
Section: Mir-365 Suppressed Liver Cscs Expansionsupporting
confidence: 81%
“…It was reported that the stem cell associated genes, including OCT4, SOX-2 and Nanog and so on, have important roles in liver CSCs regulation. [25][26][27] As expected, miR-365 overexpression downregulated the expression of stemness-associated genes ( Figures 3A and 3B) and liver CSC markers in hepatoma cells ( Figures 3C and 3D), which further supported that miR-365 could inhibit liver CSCs expansion.…”
Section: Mir-365 Suppressed Liver Cscs Expansionsupporting
confidence: 81%
“…POU5F1 has been studied for a long period of time as a well-known CSCs marker, which participates in tumor invasion, differentiation and recurrence [67]. A growing number of researches have suggested the prognostic value of POU5F1 in various malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Исследования в области биомаркеров радиорезистентности опухолевых клеток вызывают большой научный интерес [20][21][22][23][24]. Все биомаркеры ответа опухоли на лучевую терапию можно разделить на три группы:…”
Section: молекулярные биохимические и другие маркеры прогноза лечениunclassified